A Multi-scenario prospection of urban change - the case of urban growth in the Algarve - Eric De Noronha Vaz; Peter Nijkamp; Marco Painho; Mario Caetano (European Regional Science Association (ERSA), 2010)
The Algarve faces unprecedented challenges resulting from increase of urban sprawl and population density along its coastal perimeters. A growing loss of ecosystems and natural landscapes have led to major asymmetries between the interior of the Algarve and the littoral areas. The depletion of natural resources taken for granted during the sixties, are conveying to the degradation of landscape, while the formerly beautiful region of the Algarve is losing its tourist attractions, largely explored since the latter. Loss of agricultural land to urban areas, has not only been a reality in Portugal, but is a common problem in peri-urban Europe and is overshadowing sustainable development. This paper aims to analyze the land-use change tendencies for the Algarve region from the beginning of the nineties up to 2020. By using a multi-scenario perspective of weight drivers such as agriculture, coastal proximity, urban proximity, population density and road networks, an Analytical Hierarchy Process will be applied to form three growth patterns for urban propensity within the coming 10 years and expanding over a total time frame of 30 years. The novelty of this approach is shared by the usage of story-lines which generate three distinct scenarios: More Ecological, Business as Usual and Economic Reasoning (maximization of economic growth). While story-lines are naturally qualitative, this methodology proposes a quantitative validation of qualitative information, giving a much more accurate result of current trends of urban growth and environmental change in the Algarve. The projection of future land-use is managed through the CORINE Land Cover spatial databases and iterations of cellular automata with the storylines, which shall allow the projection of future urban growth. By understanding the different path-tendencies of urban growth for the region, better decision-making can be done, as to avoid unbalanced city growth, bringing forth more sustainable cities within natural landscapes.
Keywords: 330; Urban Growth; Algarve; CORINE Land Cover; Scenario Modelin